Epidemiological profile of colorectal cancer patients at an oncology center in Rio Grande do Sul - Brazil (Revista Contexto & Saúde, 2025)
Objective: To describe the epidemiological profile of patients diagnosed with colorectal cancer (CRC) in the Vale do Taquari region, Rio Grande do Sul (RS), Brazil. Methods: This is a descriptive, retrospective study based on the analysis of medical records from patients diagnosed with CRC between 2017 and 2021. Descriptive statistical methods were employed. To compare proportions between clinical variables, such as staging, metastasis, and outcomes, and their associations with sex, age, and educational level, Pearson’s chi-square test and Fisher’s exact test were applied, as appropriate. Results: The sample comprised 252 medical records. The study population was predominantly male (59.1%), in their sixties (38.9%), White (94.4%), with 8 to 10 years of education (51.6%), and with a family history of cancer in 29.8% of cases. Most diagnoses were made via colonoscopy (69.9%), with adenocarcinoma (96.8%), histological grade 2 (62.3%), and clinical stage IIA (21.9%). Metastases were present in 38.1% of cases. The most frequently indicated treatment approach was adjuvant therapy (31.4%). An educational level of 8 to 10 years was proportionally more frequent among fatal cases (X² = 43.9; P = 0.029). The presence of metastasis showed a statistically significant association in the 60–69 and 70–79 age groups (X² = 14.8; P = 0.022). Conclusion: The epidemiological profile of CRC in the Vale do Taquari region, RS, Brazil was outlined, underscoring the importance of public policies for timely diagnosis and treatment, as well as the implementation of effective CRC screening programs.
Keywords: colorectal neoplasms; epidemiology; diagnosis